Evaluation of Factors Affecting Credit Default Risk in Banking in Turkey - Şahin, Hülya (Journal of Statistics and Actuarial Research, 2024)
Purpose: The aim of the study was to analyze the evaluation of factors affecting credit default risk in banking in Turkey. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Credit default risk in Turkish banking emphasize key factors: macroeconomic indicators like GDP growth and inflation, effective loan portfolio management practices such as credit scoring models, rigorous risk assessments, and regulatory oversight. Borrower-specific factors like income stability, debt-to-income ratio, and credit history are also critical in predicting defaults. These insights underscore the intricate balance required to manage credit risk effectively within Turkey's banking sector. Unique Contribution to Theory, Practice and Policy: Merton's structural credit risk model, agency theory & capital structure theory may be used to anchor future studies on analyze the evaluation of factors affecting credit default risk in banking in Turkey. Develop and implement sophisticated risk assessment tools that combine quantitative models with qualitative insights. Advocate for regulatory reforms that promote transparency and accountability in credit risk management practices.